Does age matter? Examining career commitment as a moderator in the relationship between age‐related HR/D practices and subjective career success for younger versus older academic staff. (18th October 2021) - Van der Heijden, Beatrice I. J. M.; Veld, Monique; Heres, Leonie
Abstract: Building upon the job demands–resources framework and employing an interactionist perspective, the purpose of this scholarly work was to investigate the relationship between age‐related HR/D practices (being a contextual antecedent) and career commitment (being a personal antecedent), and the interaction between these two, on the one hand, and subjective career experiences, on the other hand. Moreover, elaborating on life‐span developmental theories and earlier empirical work on aging at work, this study also examined whether this relationship was moderated by age category (younger workers [<50 years] vs. their older counterparts [≥50 years]). An online self‐report questionnaire with thoroughly validated measures was distributed among academic staff employees ( N  = 139). The results partially supported the specific study assumptions. Concrete, age‐related HR/D practices add significantly to academics' subjective career success. Contradictory to our expectations, we could neither find a main effect of career commitment nor for its interaction with age‐related HR/D practices in the light of subjective career success. Results from the multigroup analyses indicate that, in reality, the above results may apply only to older academics (≥50 years). Possible explanations for this outcome are discussed. This study extends past career research by applying an interactionist perspective (context: age‐related HR/D practices; person: career commitment) approach for explaining subjectively experienced career success. The results of this scholarly work provide useful insights for protecting and further enhancing the sustainability of careers in academia, which is of upmost importance in nowadays' labor markets in this occupational sector.